Muslims, bio-cultural perspective - Rizvi, S. H. M. (B.R. Pub. Corp. ; Distributed by D.K. Publishers' Distributors, 1984)
Study of the ethnic composition of Indian Muslims from anthropological perspective; restricted to selected samples in Lucknow City.